Simple Monetary Policy Rules and Exchange Rate Uncertainty - Kai Leitemo; Ulf Sod̈erstrom̈ (Norges Bank, 2001)
We analyze the performance and robustness of some common simple rules for monetary policy in a New-Keynesian open economy model under different assumptions about the exchange rate model. Adding the exchange rate to an optimized Taylor rule gives only small improvements in terms of economic stability in most model configurations. The Taylor rule is also slightly more robust to uncertainty about the exchange rate model than are rules that respond to the rate of exchange rate depreciation. Our results thus indicate that the Taylor rule may be sufficient to stabilize a small open economy, also under exchange rate model uncertainty.
hdl:11250/2498710
Keywords: E52; E58; F41; 330; open economy; exchange rate determination; model uncertainty; robustness of policy rules